2017
DOI: 10.3382/ps/pex026
|View full text |Cite
|
Sign up to set email alerts
|

Rearing system affects prevalence of keel-bone damage in laying hens: a longitudinal study of four consecutive flocks

Abstract: High flock-level prevalence of keel-bone fractures and deviations in laying hens are commonly reported across various housing systems; however, few longitudinal studies exist, especially for furnished and conventional cage systems. Load-bearing exercise improves bone strength and mineral composition in laying hens and has the potential to reduce keel-bone damage, especially if exercise is allowed during critical periods of bone growth throughout the pullet rearing phase. The objective of this study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 53 publications
9
57
1
2
Order By: Relevance
“…Furthermore, many fractures in birds from alternative systems also represent diagnostic problems in the field as their localization ventrally of the caudal part of the sternum makes them difficult to reach. The most common localization at the last 5 cm of the caudal part of the tip found in our material has been reported previously [26]. Also the furculum has been reported to be commonly affected [4].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Furthermore, many fractures in birds from alternative systems also represent diagnostic problems in the field as their localization ventrally of the caudal part of the sternum makes them difficult to reach. The most common localization at the last 5 cm of the caudal part of the tip found in our material has been reported previously [26]. Also the furculum has been reported to be commonly affected [4].…”
Section: Discussionsupporting
confidence: 67%
“…Influx of inflammatory cells was absent in all birds which is characteristic for stress and greenstick fractures where a constant stress impedes healing. Greenstick fractures have been suggested previously [26] but this study is the first to show that the fractures indeed do resemble this type of fracture due to their histopathological appearance.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This coincides with observations on commercial farms that assessed damage via both dissection (Kolakshyapati et al, 2019) and palpation (Larsen et al, 2018) and found no association between individual ranging and keel damage. It was expected that rearing with structural enrichments may have reduced the later occurrence of fractures (Casey-Trott et al, 2017b), but this was not supported by the current study. The actual relationship between range use and keel damage might be inconclusive because painful keel fractures might prevent birds passing through the pop holes (Richards et al, 2012) and ultimately reduces range access.…”
Section: Discussioncontrasting
confidence: 86%